Estrés laboral y su efecto negativo en la conducta de un adulto de 27 años de la ciudad de Babahoyo - Carvajal Mera, Génesis Jamileth (2023)
The present case study was carried out with the objective of determining if work stress negatively affects the behavior of a 27-year-old adult from the city of Babahoyo. All this was carried out through the use of the clinical history, semi-structured interview, direct observation, and the application of psychological tests "Beck Depression Inventory", "Hamilton Anxiety Scale" and "Levenstein Perceived Stress Questionnaire"., in addition, of the "record of thoughts and emotions of the CBT". The qualitative methodology that was used in this work was aimed at studying the dependent and independent variables, also thanks to the implementation of CBT techniques, it was possible to meet the stated objective, on the other hand, through a therapeutic plan, it was possible to modify those variables. thoughts that the patient expressed during the psychological intervention, in this way it was possible to mitigate his behavioral changes due to the stress that he presents at work, finally the results obtained were the desired ones which were aimed at improving his quality of life, both personal as social.